Trajnostni razvoj in spremembe v gradbeništvu - Kegljevič Zagorc, Lidija (Gradbeni vestnik, 2019)
At the end of the 1980s, some European countries adopted a social development concept and called it sustainable development. By placing sustainable development as the starting point for development policies, the criteria for measuring economic development have changed, which, in addition to the economic aspect, include development in the field of environmental protection and social welfare. Sustainable development is documented in the national strategy documents of European countries as a central development guideline and is also a criterion for evaluating financing with European funds. Given the importance in the European area, it has become the starting point and a concept for establishing national development policies. The construction sector is embedded in social environment; therefore, the development and complexity of society have a major influence on the investment processes. However, sustainable development does not only bring changes in the environmental and technical area of the construction, but it also changes the role of engineers, introduces new models and practises of construction. Consequently, investment environment has altered significantly by becoming more complex and demanding.
Keywords: construction investments; gradbene investicije; sustainable development; the role of engineers; trajnostni razvoj; vloga inženirjev